2022
DOI: 10.3390/v14092043
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Infection and Pregnancy: Maternal and Neonatal Outcomes and Placental Pathology Correlations

Abstract: There is accumulating evidence on the perinatal aspects of COVID-19, but available data are still insufficient. The reports on perinatal aspects of COVID-19 have been published on a small group of patients. Vertical transmission has been noted. The SARS-CoV-2 genome can be detected in umbilical cord blood and at-term placenta, and the infants demonstrate elevated SARS-CoV-2-specific IgG and IgM antibody levels. In this work, the analysis of clinical characteristics of RT-PCR SARS-CoV-2-positive pregnant women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…In other studies, SARS-CoV-2 positive infants were also observed, but no definitive evidence of vertical transmission remains because available data are still insufficient [ 30 ]. Several studies now show that the SARS-CoV-2 genome can be detected in umbilical cord blood and placenta at term, and infants demonstrate elevated levels of SARS-CoV-2 specific IgG and IgM antibodies [ 33 , 34 ]. Although specimens of placental tissue or amniotic fluid found positive for any pathogen are considered a diagnostic sign of maternal infection, further confirmatory testing is needed before it can be deemed a sign of neonatal congenital infection [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, SARS-CoV-2 positive infants were also observed, but no definitive evidence of vertical transmission remains because available data are still insufficient [ 30 ]. Several studies now show that the SARS-CoV-2 genome can be detected in umbilical cord blood and placenta at term, and infants demonstrate elevated levels of SARS-CoV-2 specific IgG and IgM antibodies [ 33 , 34 ]. Although specimens of placental tissue or amniotic fluid found positive for any pathogen are considered a diagnostic sign of maternal infection, further confirmatory testing is needed before it can be deemed a sign of neonatal congenital infection [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…So far there are only a few reports on SARS-CoV-2 detection in newborns after infection of the mother. This includes a report on an RT-PCR SARS-CoV-2-positive infant born to an asymptomatic SARS-CoV-2-positive woman and one infant born to a SARS-CoV-2-positive mother in a retrospective Polish study on a group of 26 SARS-CoV-2-positive pregnant women who delivered during hospitalization [5,6]. However, positivity could also be due to contact with viral components during labor, e.g., maternal secretion and/or blood might come into contact with the newborn.…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiology of COVID-19 is particularly concerning in this context, as the virus is known to unbalance immune responses, including promoting the development of a "cytokine storm" (cytokine release syndrome), which can increase the risk of harm to both fetus and mother and may result in premature birth, abortion, and other fetal anomalies. The altered cytokine response to SARS-CoV-2 infection may also disrupt the normal in ammatory responses of pregnancy, increasing the risk of placental and fetal hypoxia, which can have signi cant consequences including decreased fetal growth and increased risk of premature birth, stillbirth, altered brain development, and consequent long-term cognitive and behavioral effects [15,16]. Given these concerns, understanding the full impact of COVID-19 on fetal health is essential to develop strategies to mitigate the risk of harm to fetuses and mothers.…”
Section: Introductionmentioning
confidence: 99%